Optimal sampling frequency in recording of resistance training exercises - Bardella, P.; Carrasquilla G. I.; Pozzo, M.; Tous-Fajardo, J.; Saez de Villarreal, E.; Suarez-Arrones, L. (Sports Biomechanics, 2017)
The purpose of this study was to analyse the raw lifting speed collected during four different resistance training exercises to assess the optimal sampling frequency. Eight physically active participants performed sets of Squat Jumps, Countermovement Jumps, Squats and Bench Presses at a maximal lifting speed. A linear encoder was used to measure the instantaneous speed at a 200Hz sampling rate. Subsequently, the power spectrum of the signal was computed by evaluating its Discrete Fourier Transform. The sampling frequency needed to reconstruct the signals with an error of less than 0.1% wasf99.9=11.615±2.680Hz for the exercise exhibiting the largest bandwidth, with the absolute highest individual value being 17.467Hz.There was no difference between sets in any of the exercises. Using the closest integer sampling frequency value (25Hz) yielded a reconstruction of the signal up to 99.975±0.025% of its total in the worst case. In conclusion, a sampling rate of 25Hz or above is more than adequate to record raw speed data and compute power during resistance training exercises, even under the most extreme circumstances during explosive exercises. Higher sampling frequencies provide no increase in the recording precision and may instead have adverse effects on the overall data quality. ABSTRACT FROM AUTHOR